2016
DOI: 10.2177/jsci.39.145
|View full text |Cite
|
Sign up to set email alerts
|

A case of systemic lupus erythematosus (SLE) following Human papillomavirus (HPV) vaccination

Abstract: A 15-year-old young woman received the Human papillomavirus (HPV) vaccines. Following the second HPV vaccination, intermittent fever, myalgia, arthritis and malar rash developed, and she was admitted to our hospital. Laboratory studies showed positive results for antinuclear antibody, anti-dsDNA antibody and anti-Sm antibody. Systemic lupus erythematosus (SLE) was diagnosed according to the Systemic Lupus International Collaborative Clinics 2012. Magnetic resonance imaging showed abnormal hyperintense areas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Overall, the immunogenicity of the HPV vaccine was similar in patients with SLE and controls, without significant safety signals in patients with SLE 30 177–179. Notably, concerns regarding the safety of HPV vaccine have been raised based by case reports and case series on the onset of autoimmune diseases following HPV vaccination 180–185. Population based studies have consistently shown that quadrivalent HPV vaccine was not associated with increased incidence of new-onset autoimmune disease in girls and women with pre-existing autoimmune disease 186–188.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the immunogenicity of the HPV vaccine was similar in patients with SLE and controls, without significant safety signals in patients with SLE 30 177–179. Notably, concerns regarding the safety of HPV vaccine have been raised based by case reports and case series on the onset of autoimmune diseases following HPV vaccination 180–185. Population based studies have consistently shown that quadrivalent HPV vaccine was not associated with increased incidence of new-onset autoimmune disease in girls and women with pre-existing autoimmune disease 186–188.…”
Section: Resultsmentioning
confidence: 99%
“…While some of the aforementioned studies report no significant association between SLE and HPV vaccines, several case reports have been published describing disease onset following vaccination. [95][96][97] Although case reports describing temporal association do not provide proof of causation, these reports are complemented by more recent publications relating to large-scale data. 98,99 Of note, a case-control analysis of reports submitted to the US Vaccine adverse event reporting system compared 48 816 reports of SLE to 21 998 controls (reporting adverse events other than SLE).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Reports in the literature describe new-onset SLE, lupus-like syndromes, and exacerbations of underlying autoimmune disease following HPV vaccine administration [73, 74]. However, most of these patients had personal or family history of autoimmune diseases, making them more genetically susceptible to autoimmunity [75, 76]. A case-control study based on reports to the VAERS database from 2006 to 2014 included 28 reports of SLE developing among female HPV vaccine recipients and an odds ratio of 7.626 (95% CI 3.385–19.366) for development of SLE following administration of quadrivalent HPV vaccine [77, 78].…”
Section: Human Papilloma Virus (Hpv) Vaccinementioning
confidence: 99%